Estimation of genetic variability parameters in aloe (Aloe barbadensis Mill.) genotypes to improve economic traits (Indian Journal of Arid Horticulture, 2025)
A study was conducted on twenty-six accessions of Aloe barbadensis Mill. at ICAR DMAPR, Boriavi, from 2019 to 2021 to assess morphological, chemical, and yield traits for identifying elite lines suitable for herbal drugs and cosmetics. Significant variation among accessions was observed among the evaluated genotypes. IC 310623 demonstrated superior gel and aloin yield, with high aloin content, making it ideal for medicinal and cosmetic applications. High genetic and phenotypic coefficients of variation (GCV and PCV) were noted for leaf thickness and exudates yield per plant, suggesting that direct selection for these traits could enhance future breeding programs. This study identifies promising accessions with potential for commercial exploitation in herbal and cosmetic industries.
Keywords: Genetic variability; aloin; yield; Aloe barbadensis